A Study on Situation of National Identity Card in Nepal: implications and challenges - Pandey, Romkant; Diyal, Suresh Bahadur (Educational Journal, 2023)
"A Study on the Implications and Challenges of National Identity Card in Bhaktapur, Nepal" is the title of a paper that focuses on looking into how biometric data is collected for identification and verification purposes, especially when it comes to age. The main goals of this study are to look into how the National Identity Card is being used in Nepal and to look into the challenges and problems that come with using the National Identity Card there. The numbers show how the responses were spread out among different age groups, with a focus on those who actively participated. It talks about Nepal's culture and racial variety by stating that the people who answered the survey were from different groups, like the Brahmin, Kshetri, and Janajati. It shows how important it is for the government to keep an eye on different systems, and it emphasizes how important it is for the home ministry to be careful and aware of other ministries and functional units. The phrase stresses how important it is to recognize software and technology for protecting people's privacy, as the Constitution of Nepal, 2072, says that everyone has the right to privacy. It also says that information about the public and the state can be shared, but personal information and actions must be kept safe. Things look like the people of Nepal agree with these rules and conditions. The line also talks about the Right to Information Act, the Right to Duplicate Act, and the Evidence Act of Nepal as ways to get back lost public papers. In the end, it stresses how important it is for central ministries to work together to provide services to the people in a Federal Republic of Nepal. This is especially true when it comes to issuing national ID cards with the help of the home ministry and suggestions from local governments.